DECODING CONSUMER CHOICES: INSIGHTS FROM DESCRIPTIVE STATISTICS IN BEHAVIOR ANALYSIS - Reda A. Mohammad a, *, Farah Y. F. Abdelkhair b, Yasir T. A. Attico c, Abdullah Bindawas, d Falah M. F. Alkhateeb e; Ayman H. Ahmed f (Chelonian Research Foundation, 2022)
Consumer choices play a pivotal role in shaping individual behavior and the broader economic landscape, necessitating an understanding of the factors driving these choices for effective marketing and policymaking. The research aims to explore the significance of descriptive statistics in behavior analysis, pinpoint the primary factors influencing consumer choices, and assess how consumer behavior shapes market dynamics and contributes to overall economic growth. The research methodology involves an extensive literature review to establish a foundational understanding of consumer behavior analysis and the application of descriptive statistics. Meticulous selection of descriptive statistics, including mean, median, mode, standard deviation, and frequency distributions, is based on insights from the literature review. Primary data collection through a structured survey, spanning five years with 10,000 individual responses from diverse demographics, is followed by thorough data analysis using descriptive statistics, regression analysis, and real-life case studies. The findings highlight the importance of targeted marketing strategies based on demographic characteristics, with Electronics emerging as a significant preference. The positive correlation between age and preferences for Electronics, market share analysis, and economic growth projections underscore the practical applications of descriptive statistics. By comparing real-world case studies, our research illustrates the transformative potential for businesses that embrace data-driven insights and the risks faced by those neglecting such approaches. This study contributes to a deeper understanding of consumer behavior and emphasizes the actionable nature of descriptive statistics in shaping effective marketing strategies and fostering economic development. Keywords: Behavior analysis; descriptive statistics; marketing strategies; market dynamics; economic growth; Electronics preference